PHYSIOLOGICAL POTENTIAL OF SEED AND WATER AVAILABILITY ON GERMINATION AND EARLY GROWTH OF SOYBEAN - VAZQUEZ, G. H.; ASSIS, A. V. DE (Revista Brasileira de Engenharia de Biossistemas, 2011)
The experiment was conducted in a greenhouse at UNICASTELO in Fernandópolis/SP with seeds of hybrid NK 7059 RR. The experimental design used was the completely randomized in factorial arrangement 6 x 4, i.e. six lots with germination of 76, 83, 90, 91, 97 and 100% and four levels of moisture in the soil by irrigation (100, 75, 50 and 25% of the available water capacity of the soil), with four replicates of 50 seeds. The data obtained allowed to conclude that: the irrigation level of 75% of field capacity provides the largest percentages of emergence of soybean seedlings; the higher is the physiological potential of seeds, the higher the percentage and speed of emergence and height of seedlings, with no interference on the dry matter of seedlings and finally, the higher the water availability in the soil, the greater the weight of dry matter of soybean seedlings.